An evaluative study of the Department of Social Welfare and Development's self-employment assistance program - Quieta, Romeo C. (1989)
One of the government's anti-poverty program is the Self -EmploymentAssistance Program (SEAP) which is administered and implemented by the Department of Social Welfare and Development (DSWD). SEAP provides capital assistance to the bottom 30% of the population to enable them to undertake income-producing projects as their main or supplemental income. This study ascertains whether the SEAP has contributed to the improvement of the poor's quality of life. Five hundred (500) respondents, representing the population of Luzon, Visayas and Mindanao comprised the sample of this study. Findings indicated that SEAP has indeed uplifted the well-being of the poor. Prior to SEAP, they could not provide basic needs (e.g., medicine, education, etc.). The program is at least reasonable and cost-effective but the success of the program and its improvement require. the availability of more funds. The study reveals that bigger benefits were received by those who were able to loan more than once. Moreover, social workers who could supervise, give information, motivate and assist beneficiaries are needed to ensure that more income could be generated from the SEAP.
Keywords: Livelihood programs; Social services; Self -Employment Assistance Program (SEAP); Department of Social Welfare and Development